Alloexidiopsis gen. nov., A Revision of Generic Delimitation in Auriculariales (Basidiomycota) - Liu, Shi-Liang; Shen, Zi-Qi; Li, Qian-Zhu; Liu, Xiang-Yang; Zhou, Li-Wei (Frontiers in Microbiology, 2022)
Auriculariales is a fungal order with highly diverse morphological traits of basidiomes, which partially leads to a poor understanding of its taxonomic system at the generic level. To identify our recently collected specimens of Auriculariales to a species level, we perform a comprehensive phylogenetic analysis of the generic relationships in Auriculariales. In association with morphological characteristics, a new genus Alloexidiopsis belonging to Auriculariaceae is erected with two new species, namely, A. australiensis and A. schistacea. Moreover, Exidiopsis calcea separated from the generic type E. effusa and Heteroradulum niveum and H. yunnanense recently inaccurately described as members of Heteroradulum are recovered in the clade of Alloexidiopsis. These three species are thus transferred to this new genus. One collection of Exidiopsis grisea also falls in the clade of Alloexidiopsis, whereas another collection of this species is separated far from Alloexidiopsis and E. effusa. Since we have no collection to confirm the species identity of E. grisea, its generic position is uncertain. The main taxonomic morphological differences among Alloexidiopsis and related corticioid genera in Auriculariales are summarized. A key to all the five accepted species of Alloexidiopsis is provided. As two unnamed lineages exist in Alloexidiopsis besides the abovementioned five species, it is assumed that more new species will be revealed from this genus under its current circumscription.